Pre-operative MRI measurements versus anthropometric data: Which is more accurate in predicting 4-stranded hamstring graft size in anterior cruciate ligament reconstruction? - Thwin, Lynn (Asia Pac J Sports Med Arthrosc Rehabil Technol, 2020)
BACKGROUND/OBJECTIVE: Graft diameter has been shown to play an important role in anterior cruciate ligament (ACL) autograft failure rates. The roles of pre-operative MRI measurement of graft size and anthropometric data have been studied in the prediction of hamstring graft size. Pre-operative knowledge of hamstring graft diameter allows surgeons to perform better surgical planning and provides an opportunity to discuss with patients on alternative graft options such as allografts should the need arises. The purpose of this study was to compare the accuracy of pre-operative anthropometric data and MRI measurements in the prediction of 4-stranded hamstring autograft size in anterior cruciate ligament reconstruction. METHOD: This was a cohort study involving 141 subjects (115 males and 26 females) who underwent a single bundle ACL reconstruction utilising a 4-stranded hamstring graft by a single surgeon from 2008 to 2012. Pre-operatively, the height, weight, body mass index (BMI), age, gender and smoking status was recorded. The MRI scans used for diagnosis were utilized to measure the gracilis (GT) and semi-tendinosus (ST) cross sectional area (CSA). RESULT: We found the strongest correlation between Combined (ST + GT) CSA and intra-operative graft size (r = 0.596, p < 0.001). This was followed by ST CSA (r = 0.570,p < 0.001), Body surface area (r = 0.507,p < 0.001), and GT CSA (r = 0.460,p < 0.001). No significant correlation was found between 2 anthropometric data (Age and BMI). There was also no significant difference between different strengths of MRIs (1.5T vs 3.0T) in determining the intra-operative graft size (p = 0.438). CONCLUSION: We conclude that pre-operative MRI is superior to anthropometric variables in predicting the size of 4-stranded hamstring autografts used in ACL reconstruction.